Distribution of Metabolic Diseases and Demographic Characteristics of Pilgrims in 2024 Hajj: A Descriptive Cross-sectional Study from the Ministry of Health in Saudi Arabia (Asian Journal of Pharmaceutics (AJP), 2025)
Religious pilgrimages, such as the Hajj, are well-publicized mass gatherings that attractmillions of people worldwide. These events can strain the public health resources of the host nation, requiring ahigh level of readiness and response capacity. Therefore, this study aims to evaluate the Distribution of metabolicdiseases and demographic characteristics of pilgrims in the 2024 Hajj. Materials and Methods: A cross-sectionalstudy was conducted among Hajj pilgrims in Saudi Arabia from June to July 2024. Data were collected usingpre-validated questionnaires. The study included pilgrims from diverse backgrounds, both male and female, whowere able to complete the questionnaires. The data were analyzed using the Statistical Package for Social Sciencesversion 27. A Chi-square or Fisher’s exact test was used to determine the association between variables, with aP < 0.05 considered statistically significant. Results: Out of the 4,721 pilgrims who responded, 48.9% were male(n = 2,308) while 51.1% were female. The mean age was 51.74 ± 13.92 years with the most reported metabolicdiseases being diabetes, 16.3% followed by obesity, 0.7%. The largest age group was 60 years old (5.4%; n = 253),followed by 50 (4.5%; n = 211) and 55 (4.2%; n = 199) years old. Regarding education, 23.4% had a universitydegree, while 17.2% were literate. In terms of nationality, 13.1% were from Morocco (n = 617), followed byYemen (8.7%; n = 409), Iraq (8.6%; n = 405), Indonesia (8.1%; n = 384), Algeria (7.5%; n = 355), Pakistan (6.4%;n = 302), Egypt (6.1%; n = 288), Bangladesh (5.8%; n = 275), and China (5.8%; n = 274). There was a significantdifference in gender distribution by nationality (P = 0.001). Conclusion: This study highlights the distribution ofpilgrims across nationalities, gender, age, education, and various chronic diseases. The confirmation of the variousdemographics present during Hajj, the Saudi Arabian leadership to create targeted interventions based on this datato provide adequate facilities.